Medical value tourism: A revival for post covid tourism industry in India - Riya Raju George; S Sunil; K Vijayan; Shanimon Saleem (Borneo Novelty Publishing, 2025)
Purpose - This paper aims to examine the economic potential, benefits, and cost-savings associated with India’s growing medical value tourism sector. It also explores how the healthcare industry, as a major driver of foreign direct investment, contributes to India’s broader goals of economic growth and employment generation. Methodology - The study employs a descriptive and analytical approach based on secondary data from government reports, budget documents, and tourism revenue statistics. It analyses the performance of the medical tourism industry before, during, and after the COVID-19 pandemic to understand growth trends and recovery patterns. Findings - India has emerged as a leading destination for medical value tourism due to its high-quality healthcare services, advanced medical infrastructure, and cost competitiveness compared to developed nations. Tourism revenue in India peaked at ₹20.342 trillion in 2018 but declined to ₹10.024 trillion by 2020 because of the pandemic, reflecting a negative average growth rate of -1% from 2015 to 2019. However, the sector began to recover, reaching an estimated ₹15.9 trillion in 2022, with an average growth rate of 39% during 2020–2021. This rebound highlights the resilience of the tourism sector and the increasing contribution of medical tourism to economic revitalization. Originality/Value - This paper provides a focused analysis of India’s medical value tourism as a strategic component of national economic policy and post-pandemic recovery. It highlights the integration of healthcare excellence, affordability, and government initiatives—such as the Union Budget 2023’s mission mode for tourism—as key enablers of sustainable growth in India’s tourism and healthcare sectors.